Psychosocial predictors of adolescent aggression - Ahmad Fauzi, Fatimah; Mohd Zulkefli, Nor Afiah; Minhat, Halimatus Sakdiah; Ahmad, Norliza (Universiti Putra Malaysia Press, 2019)
Aggression is one of the most common Paediatric Psychiatric emergency problems presented in healthcare services with major public health impacts. The aim of this review is to determine the psychosocial predictors of adolescent aggression. Systematic review on observational study designs were conducted. Recent five years English published journal articles (2014-2018) were searched in three databases (Science Direct, PubMed and EBSCO) from April 2018 until May 2018. The final 15 articles (seven prospective cohort, eight cross-sectional studies) were included in the systematic review. Psychological predictors were mainly on the personality traits and emotional problems experienced by the adolescents including callous-unemotional traits, hostility, anger, and low empathy. Self-control was found to be protective against adolescent aggression. Social predictors that contribute to the aggression among adolescents according to the highest reported number of articles were peer influence, followed by school climate, substance use, neighbourhood influence, family, and parent factors. In conclusion, psychosocial predictors of adolescent aggression include both Psychological Factors; mainly personality traits and emotional problems, and Social Factors; mainly peer influence and substance use. This warrants for more holistic approach in dealing with aggressive adolescents that can be applied in more targeted and focused intervention strategy deliveries.